Системний підхід до планування об’єктів підземного будівництва за методологіями передбачення та когнітивного моделювання - Pankratova, Nataliya; Pankratov, Vladimir (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2022)
The system approach to the underground construction objects planning based on foresight and cognitive modeling methodologies is proposed. Using the foresight methodology allows with the help of expert estimation procedures to identify critical technologies and build alternatives of scenarios with quantitative characteristics. For the justified implementation of a particular scenario the cognitive modelling is used, which allows to build causal relationships based on knowledge and experience, understand and analyze the behaviour of a complex system for a strategic perspective with a large number of interconnections and interdependencies. The suggested system approach allows planning of underground objects on the basis of reasonable scenarios selection and justification of their creation priority.